2015
DOI: 10.1080/09500693.2015.1022625
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Effects of School-, Classroom-, and Student-Level Factors on the Science Performance of Eighth-Grade Taiwanese Students

Abstract: This study was conducted to understand the effect of student-, classroom-, and school-level factors on the science performance of 8th-grade Taiwanese students in the Trends in International Mathematics and Science Study (TIMSS) 2011 by using multilevel analysis. A total of 5,042 students from 153 classrooms of 150 schools participated in the TIMSS 2011 study, in which they were required to complete questionnaires. A 3-level multilevel analysis was used to assess the influence of factors at 3 levels on the scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
1
17
0
4
Order By: Relevance
“…On the other hand, Students Like Learning (SL), Students Confident (SC) and Students Value (SV) scales are created separately for each specific content. Except SSB, numerous studies have been conducted to investigate the importance of these scales on students' success (Kaya & Rice, 2010;Lai, Ye, & Chang, 2008;Smith, Pasero, & McKenna, 2014;Thomson, 2008;Tsai & Yang, 2015;Topçu, Erbilgin, & Arıkan, 2016). Since SSB scale is newly created, a limited number of studies dealing with its effect have been available (Hu, Leung, & Chen, 2018;Smith et al, 2019).…”
Section: Factors Affecting Science Successmentioning
confidence: 99%
“…On the other hand, Students Like Learning (SL), Students Confident (SC) and Students Value (SV) scales are created separately for each specific content. Except SSB, numerous studies have been conducted to investigate the importance of these scales on students' success (Kaya & Rice, 2010;Lai, Ye, & Chang, 2008;Smith, Pasero, & McKenna, 2014;Thomson, 2008;Tsai & Yang, 2015;Topçu, Erbilgin, & Arıkan, 2016). Since SSB scale is newly created, a limited number of studies dealing with its effect have been available (Hu, Leung, & Chen, 2018;Smith et al, 2019).…”
Section: Factors Affecting Science Successmentioning
confidence: 99%
“…Several studies indicated that teacher-related factors have effects of various magnitudes on student achievement in mathematics (e.g., Rivkin et al 2005;Akiba et al 2007;Akyüz and Berberoglu 2010;Tsai and Yang 2015;Winnaar et al 2015). For example, De Witte and Van Klaveren (2014), using data from Dutch students participating in TIMSS 2003, found that high test scores are associated with teaching styles that emphasize problem solving and homework.…”
Section: School-level Variables In the Iea Studiesmentioning
confidence: 99%
“…The relationship between socioeconomic factors and OL has not been extensively discussed in the literature. Furthermore, parental education level is usually considered one of the most stable socioeconomic factors because it establishes its influence on children at a young age, which then remains consistent over time [11,12]. Kalender and Berberoglu regarded parental education level as a critical indicator of socioeconomic status and determined that it was a substantial variance in student learning outcomes [13].…”
Section: Relationship Between Student-level Predictors and Olmentioning
confidence: 99%
“…The objective of the present study was to use hierarchical linear model to determine the influence of the personal characteristics of Taiwanese senior high school students and school-level predictors on their OL performance. Hierarchical linear modeling is the most appropriate statistical method for analyzing data that are organized in more than one level [11,22]. Thus, this study employed hierarchical linear model to determine factors influencing OL from the perspectives of student and school levels.…”
Section: Research Purposesmentioning
confidence: 99%